Theoretical and methodological foundations for designing learning environments in Cuban Higher Medical Education - José Aurelio Diaz Quiñones; María Lina Valdés Gómez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
The Cuban Higher Medical Education is subject to the current society knowledge and information demands, characterized by its complexity, uncertainty, globalization, development of information technologies and knowledge obsolescence, which determine changes in different aspects of the places where future professionals will work. The theoretical and methodological foundation is then paramount to support on the job teaching, teaching and research practices from learning environments which enable student centered teaching processes from a developing perspective. This work is aimed at systematizing the main aspects which allow leading a process with these characteristics. Systematization, documentary analysis and triangulation were used. It is concluded that the essential dynamics of learning environments structure and function and the proper conception of activity and communication, are core systematizing axes typical of these environments in the teaching learning organizational forms, mainly those of on the job education, oriented to acquiring the necessary contents in this 21st century society, from a student centered developing perspective.